The Correlation of Students’ Perceptions About Speaking Skills Demonstration Method With Learning Outcomes of English Subject in Binjai “Ex School” Tutoring - Mariana; Rudi Purwana (International Journal of Cultural and Social Science, 2021)
The demonstration method is a way of presenting information in KBM by demonstrating how to do something with a clear visual explanation of the process. Students have different perceptions about the demonstration method delivered by the teacher. The purpose of the research was to determine the relationship between students' perceptions of the speaking skill demonstration method and the learning outcomes of English subjects at the "Ex School" Binjai Tutoring. This type of research is an analytic survey with a cross sectional approach. The results of the validity test obtained 21 valid statements with a range of Sig values. (2-tailed) (0.00-0.04) < = 0.05. The population in this study was 64 students, the sampling technique was saturated, that is, all students became the research sample. Direct data collection by researchers by distributing questionnaires directly to respondents. From the research results obtained the majority of students with negative perception category 36 students (56.2%), with very good learning outcomes 0 students (0%), good 2 students (3.1%), enough 31 students (48.4%) and less than 3 students (4.7%), minority students with positive perceptions 28 students (43.8%) with very good learning outcomes 0 students (0%), good 7 students (10.9%), enough 21 students ( 32.8%) and less 0 students (0%) . From the results of the chi-square test, the Asymp sig value (0.033) < value = 0.05. So it can be concluded that there is a relationship between students' perceptions of the speaking skill demonstration method and the learning outcomes of English subjects at the "Ex School" Binjai Tutoring. Therefore, it is expected that students can give positive perceptions about the demonstration method delivered by educators so that the learning outcomes obtained will be better.